Effectiveness of Curcumin Supplementation in feed on liver productivity and reproductive performance of female carp Cyprinus carpio L. : Effectiveness of Curcumin Supplementation in feed on liver productivity and reproductive performance of female carp Cyprinus carpio L. - Livana Dethris Rawung; Jacson Saruan (Indonesian Biodiversity Journal, 2020)
The availability of quality seeds, on time with large amounts is a major problem in freshwater aquaculture. Supplementation of curcumin in female carp aims to increase the reproductive productivity of fish through increased activity of the liver in the synthesis of vitellogenin, a precursor of egg yolk, that play a role in the growth and development of eggs until larvae. This study used 25 female carp, which supplemented with curcuminat several doses: 0; 2.5; 5; 10; and 20 g of curcumin/kg of feed. The collected data was analyzed using a completely randomized design (CRD). The results showed that supplementation of curcumin female carp significantly (p<0.05) affected the malondialdehyde(MDA) concentration of liver, estradiol hormone in the blood, gonadosomatic index, relative fecundity, and larval survival, but did not significantly (p>0.05) affect the superoxide dismutase (SOD), vitellogenin concentration in blood and egg diameter. The study showed that the supplementation of curcumin prevents liver damage showed by a decreased level of liver MDA. The supplementation of curcumin with a dose of 5 g/kg of feed optimizes the productivity and reproductive performance of carp by increasing the production of vitellogenin, the diameter of egg, and the number of survival larva through optimizing the performance of the fish liver.